Green Roofs as a Nature-Based Solution to Mitigate Urban Heating During a Heatwave Event in the City of Athens, Greece - Spyrou, Christos; Koukoula, Marika; Saviolakis, Pantelis-Manolis; Zerefos, Christos; Loupis, Michael; Masouras, Charis; Pappa, Aikaterini; Katsafados, Petros (Sustainability, 2024)
This study investigates the impact of green roof (GR) implementations as a mitigation strategy for urban heating during an extreme heat wave event in Athens, Greece, from 28 July to 5 August 2021. Three GR scenarios were simulated, namely 100% grass coverage, 100% sedum coverage, and 50% grass coverage, using the Weather Research and Forecasting model (WRF) in conjunction with the multi-layer urban-canopy-model BEP&BEM (Building Effect Parameterization/Building Energy Model) and extra urban land-use categories from Local Climate Zones (LCZ). Based on the results, GRs alter the local heat balance in the Greater Area of Athens (GAA), leading to a total temperature reduction. The 100% grass coverage proved to be the most effective, particularly during daytime, reducing the 2 m temperature field by approximately 0.7 ∘C (mean value) in the GAA. In some locations, temperature reductions exceeded 2 ∘C, depending on the local characteristics and the direction of the prevailing winds. Grass offered superior cooling effects compared to sedum, although sedum is more resilient to dry and moderate climates. The extent of vegetation coverage played an important role in the effectiveness of GRs. Reducing the coverage by 50% significantly reduced the cooling benefits, highlighting the importance of maximizing vegetation coverage to achieve notable temperature reductions.